Application of UV-C Radiation in the Conservation of Minimally Processed Rocket ( Eruca sativa Mill.) - Gutierrez, Diego Ricardo (2015)
The effects of UV-C pretreatments (10, 20 and 30 kJ/m2), compared with modifiedatmosphere packaging (MAP), on sensory change, microbial and bioactiveprofile of minimally processed rocket leaves throughout 12 days at 5C were investigated.Nonirradiated samples were used as controls. All UV-C treatmentsreduced the natural microflora growth. In relation to sensory quality, all treatmentsresulted in a shelf life of 8 days. Total antioxidant activity and total phenolcontent decreased after 8 days for all treatments. Generally, UV-C slightly reducedthe initial total chlorophyll content; however, during storage, its degradation wassimilar to that of the control. It is concluded that UV-C pretreatment could beuseful to the industry to reduce the natural microflora growth, keeping the overallquality without affecting the bioactive compound profile of fresh rocket leavesduring 8 days of storage at 5C.